The discourse analysis of mobile marketing on the internet - Bárdos Anita; Szarvas Júlia (2004)
Present thesis paper is based on the research of the three most successful mobile providers in the world', namely, Nokia, Samsung and SonyEricsson. Each of these companies has a high level of web marketing and its own individual language of advertising. These companies have not only introduced their own vocabulary and style of advertising but they also reinvented a site structure which is in chime with the discourse used. Discourse analysis is "the study of the relationship between language and the context in which it is used2". I am going to prove that the structure and image of each company's site reflec s,the discourse function of the text on the pages.
Keywords: Pedagógusképzés